2020
DOI: 10.1186/s13019-020-01248-2
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term follow-up after aortic valve replacement with the Carpentier Edwards Magna Ease prosthesis

Abstract: Background: Approximately 250,000 heart valve operations are performed annually worldwide. An intensive research and development effort has led to progressively more advanced heart valve prostheses. The Carpentier-Edwards Perimount Magna Ease (CEPME) prosthesis represents the latest iteration of the Edwards Perimount series of aortic tissue valves. The current study aims to evaluate the midterm performance of this bioprosthesis. Methods: Five hundred and eighteen patients with aortic stenosis underwent aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…34 Early generations of this valve have been in clinical use since the 1980s, and subsequent generations have the same general design but with small modifications to ease supra-annular placement and to improve tissue preservation. 35 Hemodynamic performance and long-term follow-up of the Perimount valve have provided satisfactory results. 12,13,34,[36][37][38] A recent study by Lam and colleagues 34 reported an 8-year cumulative incidence of reintervention of 0.7% compared with a 10-year cumulative incidence of reintervention of 3% in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…34 Early generations of this valve have been in clinical use since the 1980s, and subsequent generations have the same general design but with small modifications to ease supra-annular placement and to improve tissue preservation. 35 Hemodynamic performance and long-term follow-up of the Perimount valve have provided satisfactory results. 12,13,34,[36][37][38] A recent study by Lam and colleagues 34 reported an 8-year cumulative incidence of reintervention of 0.7% compared with a 10-year cumulative incidence of reintervention of 3% in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…None of the patients had required reintervention. This highlights the durability of modern bioprostheses 12 …”
Section: Discussionmentioning
confidence: 91%
“…As such, we have mid‐ and long‐term performance data on the development of SVD. At our center, we recently published a study where we followed 100 consecutive patients receiving the Carpentier‐Edwards Perimount Magna Ease (CEPME) prosthesis (implanted in 76.6% of patients in the present series) 12 . At a median of 5.1 years, none of the patients had evidence of significant SVD.…”
Section: Discussionmentioning
confidence: 97%
“…The study on the Edwards PERIMOUNT aortic valve bioprostheses used in the aortic position and concerned the progenitor of INSPIRIS RESILIA aortic valve, demonstrated a low rate of valve‐related events and SVD, especially in patients aged over 60 years. In a 3‐year follow‐up of 580 patients who underwent AVR using a Carpentier‐Edwards PERIMOUNT valve, there was no evidence of SVD 26 . Although these midterm results are promising, long‐term follow‐up in 12,569 patients with PERIMOUNT valve at 10, 15, and 20 years showed that the actuarial estimates of risk for explant for SVD were 5.6%, 20%, and 45%, respectively, in patients <60 years and 1.5%, 5.1%, and 8.1%, respectively, in patients 60–80 years old 27 …”
Section: Discussionmentioning
confidence: 99%